2001
DOI: 10.1021/jp012185h
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of a CytochromebMaquette for Electron Transfer and Coupled Reactions on Electrodes

Abstract: Experimental explorations of functional mechanisms in natural electron-transfer proteins are often frustrated by their fragility and extreme complexity. We have designed and synthesized four-R-helix-bundle redox proteins, maquettes, that are much simplified and more robust than natural redox proteins and can be designed to bind onto electrode surfaces to facilitate systematic investigations. The points of interest that can be now assessed are not only the processes that govern biological assembly of equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 50 publications
7
47
0
Order By: Relevance
“…22,3840 De novo protein design has shown that the exterior of the helix bundle can be tailored with specific patterns of charge or hydrophobicity so as to facilitate insertion into vesicles, orientation at interfaces, or assembly on solid substrates, while preserving the interior of the helix bundle, that is, its designed functionality. 37,4144 …”
Section: Resultsmentioning
confidence: 99%
“…22,3840 De novo protein design has shown that the exterior of the helix bundle can be tailored with specific patterns of charge or hydrophobicity so as to facilitate insertion into vesicles, orientation at interfaces, or assembly on solid substrates, while preserving the interior of the helix bundle, that is, its designed functionality. 37,4144 …”
Section: Resultsmentioning
confidence: 99%
“…Gooding and associates have addressed aspects of this comprehensive area focusing on electrode-protein contacts via carbon nanotube contacts [28,29]. Still another novel aspect of bioelectrochemistry and protein film voltammetry is related to interfacial electrochemistry of totally synthetic proteins, particularly synthetic 4-α-helix-bundle heme proteins as developed by Dutton [30], Willner [31], Haehnel [32] and their associates. This area of design and synthesis of functional electron transfer and catalytic proteins parallels the introduction of novel physical electrochemistry, particularly in situ scanning tunnelling microscopy (in situ STM) in bioelectrochemistry, cf.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, maquettes are designed to be environmentally robust to foster the development of biochemical devices for technological applications ranging from driving catalytic redox reactions to biosensors and bioremediation. By adapting the pattern of amino acid charges on the maquette surface, the interaction with electrode surfaces and therefore the electron transfer to/from the maquettes can be readily controlled 4. However, previous surface electrochemical studies of protein maquettes have been constrained to planar electrodes4, 5 and the monolayer surface densities of self‐adsorbed maquettes provide only small, milliOD (OD, optical density units) spectroscopic signals.…”
Section: Introductionmentioning
confidence: 99%